Halo and spillover effect illustrations for selected beneficial medical devices and drugs - Brent D. Kerger; Autumn Bernal; Dennis J. Paustenbach; Gavin Huntley-Fenner (BMC, 2016)
Abstract Background Negative news media reports regarding potential health hazards of implanted medical devices and pharmaceuticals can lead to a 'negative halo effect,' a phenomenon whereby judgments about a product or product type can be unconsciously altered even though the scientific support is tenuous. To determine how a 'negative halo effect' may impact the rates of use and/or explantation of medical products, we analyzed the occurrence of such an effect on three implanted medical devices and one drug: 1) intrauterine contraceptive devices (IUDs); 2) silicone gel-filled breast implants (SGBI); 3) metal-on-metal hip implants (MoM); and 4) the drug Tysabri. Methods Data on IUD use from 1965 to 2008 were gathered from the Department of Health and Human Services Vital and Health Statistics and peer-reviewed publications. Data regarding SGBI implant and explantation rates from 1989 to 2012 were obtained from the Institute of Medicine and the American Society of Plastic Surgeons. MoM implant and explantation data were extracted from the England and Wales National Joint Registry and peer-reviewed publications. Tysabri patient data were reported by Elan Corporation or Biogen Idec Inc. Data trends for all products were compared with historical recall or withdrawal events and discussed in the context of public perceptions following such events. Results We found that common factors altered public risk perceptions and patterns of continued use. First, a negative halo effect may be driven by continuing patient anxiety despite positive clinical outcomes. Second, negative reports about one product can spill over to affect the use of dissimilar products in the same category. Third, a negative halo effect on an entire category of medical devices can be sustained regardless of the scientific findings pertaining to safety. Fourth, recovery of a product's safety reputation and prevalent use may take decades in the U.S., even while these products may exhibit widespread use and good safety records in other countries. Conclusions We conclude that the 'negative halo effect' associated with a stigma, rather than an objective risk-benefit assessment of medical products can increase negative health outcomes for patients due to reduced or inappropriate product usage.